FINTECH PAYMENT ADOPTION AMONG MICRO-ENTERPRISES: THE ROLE OF PERCEIVED RISK AND TRUST - Anissa Hakim Purwantini; Friztina Anisa (Universitas Pendidikan Indonesia, 2021)
The current adoption of fintech payment technology by MSMEs is motivated by the trend of using digital money. This study presents an investigation the factors that influence the intention to use fintech payments (e-money, e-wallet and Electronic Data Capture) in micro-enterprises. Furthermore, this study will explore more specifically the role and perceived trust and risk in fintech payment adoption. This study uses a quantitative method by distributing surveys to 136 Micro, Small and Medium Enterprises using convenience sampling technique. The results indicated that perceived usefulness, risk and trust are the important drivers of the adoption fintech payment among the micro-enterprises. The results of this study reveal interesting findings, risk perception has a significant positive effect on intentions to use fintech payments.